Boosting Cell Performance of LiNi0.8Co0.15Al0.05O2 via Surface Structure Design. Issue 50 (13th November 2019) - Zheng, Junchao; Yang, Zhuo; Dai, Alvin; Tang, Linbo; Wei, Hanxin; Li, Yunjiao; He, Zhenjiang; Lu, Jun
Abstract: Although the high energy density and environmental benignancy of LiNi0.8 Co0.15 Al0.05 O2 (NCA) holds promise for use as cathode material in Li‐ion batteries, present low rate capabilities, and fast capacity fade limit its broad commercial applications. Here, it is reported that surface modification of NCA cathode ( R‐3m ) with 5 nm‐thick nanopillar layers and Fm‐3m structures significantly improves electrode structure, morphology, and electrochemical performance. The formation of nanopillar layers increases cycling and working voltage stability of NCA by shielding the host material from hydrofluoric acid and improves structural stability with the electrolyte. The modified NCA cathode exhibits an enhanced 89% capacity retention at a rate of 1 C over that of pristine NCA (75.2%) after 150 cycles and effectively suppresses working voltage fade (a drop of 0.025 V after 300 cycles) during repeated charge–discharge cycles. In addition, the diffusion barrier of Li ions in NCA crystals at 0.80 V is noticeably smaller than that of Li ions in pristine NCA (0.87 eV). These findings demonstrate that this unique surface structure design considerably enhances cycle and rate performance of NCA, which has potential applications in other Ni‐rich layered cathode materials. Abstract : A surface design to induce the transformation of Ni 3+ to Ni 2+ and form a newly observed NiO phase in LiNi0.8 Co0.15 Al0.05 O2 cathode is proposed. This surface layer formed NiO phase with Fm‐3m structure is stable and has a lower Li‐ion diffusion barrier, which produces excellent structural stability and cycle stability. It considerably improves cycle stability, rate performance, and effectively supresses voltage decay.